Microstructure and mechanical properties of the rheoformed cylindrical part of 7075 aluminum matrix composite reinforced with nano-sized SiC particles. (15th August 2015) - Jiang, Jufu; Wang, Ying
Graphical abstract: Highlights: Cylindrical parts of nano-sized SiCp /7075 composite were rheoformed. Pressure and stirring time led to an increase of the mechanical properties. Highest mechanical properties were achieved only upon addition of 1 vol.% SiCp . Abstract: The microstructure and mechanical properties of the rheoformed parts of 7075 aluminum matrix composite were investigated. The results show that more liquid phase and spheroidal solid grains were found in the microstructures in the top and medium regions of the side wall of the rheoformed parts due to dependence of the deformation on liquid flow and flow of liquid incorporating solid grains. Yield strength and ultimate tensile strength of the rheoformed composite parts are enhanced as compared with the as-extruded and the rheoformed parts of 7075 matrix alloy. The yield strength, ultimate tensile strength and elongation of the rheoformed composite parts with T6 reach 399 MPa, 492 MPa and 9.6%, respectively. When stirring time increases from 5 min to 20 min, the mechanical properties increased due to fine-grained strengthening and a further increase more than 20 min led to a slight change. Pressure led to a significant increase of the mechanical properties due to some reduction of defects and dislocations strengthening. An increase of SiC volume fraction from 0.5% to 1% led to an improvement of yield strength and ultimate tensile strength and a further increase led to a decrease.